PERBEDAAN HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF PAIKEM DENGAN MODEL PEMBELAJARAN TALKING STICK SISWA KELAS XI IPS SMA NEGERI 14 MEDAN T.A 2022/2023 - Nurul Khairi Mawaddah; Mhd Zulkifli (Melati Institute, 2023)
Reawarch tittle: Diffrent in learning outcomes in economics using the Paikem learning and the Talking Stick learning model for class XI IPS SMA Negeri 14 Medan T.A 2022/2023. The research objective was to find out the difference between the use of the Paikem learning model and the Talking Stick learning model on economic learning outcomes. The research method uses the post-test. The population in this study were all students of class XI IPS SMA Negeri 14 Medan T.A 2022/2023. The sample in this study were students in class XI IPS-1, XI IPS-2, and IPS-3, wich consisted of 108 students. This sampling technique is total sampling here all members of the population are sampled. The research result obtained tcount = 12,17 and ttabel = 1,647, where tcount (12,17) > ttabel (1.647). Thus, Ho is rejected and Ha accepted. So it can be concluded that there are differences in the economics learning outcomes of students using the Paikem learning model using the Talking Stick learning model.